What’s the big deal? : Dealing with sexual harassment on dating apps - Shree, G. Nanthinee (Nanyang Technological University, 2021)
This paper presents “What’s The Big Deal? (WTBD)”, a first of its kind local campaign aimed at raising awareness on sexual harassment on dating apps while promoting a cultural movement away from the currently normalised social treatment of digital sexual harassment. With COVID-19 restrictions on social gatherings and entertainment venues, the dating scene in Singapore has changed drastically. Many are finding romance online through dating apps yet the potential dangers of digital dating have not been adequately explored; the combination of these factors necessitates for a campaign that brings awareness on sexual harassment on dating apps. WTBD’s campaign strategy is segmented into three pillars - Identify, Address and Combat. The three-month long campaign launched with an informative series that highlighted the various natures of sexual harassment on dating apps. To underscore the seriousness of sexual harassment on dating apps, the team released a video series comparing crowd-submitted dating app conversations and their reenactments in real life. Our campaign was well received both offline during a Fireside Chat event and on social media (@wtbd.sg) gaining over 11,000 organic impressions as of mid-March. The campaign efforts incited behavioural change in our target audience as there was an observed increase in the frequency of social conversation of sexual harassment on dating apps. This enabled social reframing of this topic to one that is understanding of its severity and user repercussions. Overall, WTBD was successful in increasing awareness and starting conversations regarding sexual harassment on dating apps.